Synergy between phorbol esters, 1-oleyl-2-acetylglycerol, urushiol, and calcium ionophore in eliciting aggregation of marine sponge cells. - Weissmann, G (Proc Natl Acad Sci U S A, 1986)
Aggregation of marine sponge cells (Microciona prolifera) resembles stimulus-response coupling of higher organisms in which activation of protein kinase C and movements of intracellular Ca provide twin signals. We now report that activators of protein kinase C (phorbol esters) and ionomycin act synergistically to aggregate sponge cells. Surprisingly--since extracellular Ca is required for integrity of the species-specific aggregation factor--synergistic aggregation proceeded in the complete absence of added extracellular Ca (2.5-20 mM EDTA). The order of activity of phorbol esters and related compounds was that of their effect on protein kinase C (phorbol myristate acetate, phorbol dibutyrate greater than phorbol diacetate much greater than phorbol, 4 alpha-phorbol). 1-Oleyl, 2-acetylglycerol a synthetic activator of protein kinase C, also showed synergy with ionomycin. Phorbol esters and 1-oleyl, 2-acetylglycerol acted in synergy with ionomycin to liberate membrane Ca as detected by decreased fluorescence of chlortetracycline in prelabeled cells. Moreover, urushiol, the toxic principle of poison ivy, but not pentadecanylcatechol, its inert analogue, showed synergy with ionomycin. Synergistic aggregation was inhibited by calmidazolium (10 microM), piroxicam (20-100 microM), and pertussis toxin (20 micrograms/ml). The data not only confirm that marine sponge cell aggregation follows the general sequence of stimulus-response coupling in the cells of higher organisms but also support, in this most ancient of multicellular creatures, the hypothesis that mobilization of intracellular Ca and activation of protein kinase C provide the twin signals for cell activation in the absence of added extracellular Ca.